Syntheses and characterization of functionalized cyclodiphosphazane-based frameworks - Sim, Ying (2019)
Cyclodiphosph(III)azanes are four-membered ring compounds, made up of alternating trivalent phosphorus and nitrogen atoms. They are generally highly air and moisture sensitive, therefore hindering their utility in many areas. Their syntheses and manipulations require strict exclusions of oxygen and moisture to minimize the possibility of oxidation and hydrolysis. Moreover, the incompatibility of cyclodiphosph(III)azanes to protic solvents and the poor solubility of organic nucleophiles of interest pose difficulties in synthetic procedures as we work towards expanding the family of functionalized cyclodiphosphazane-based frameworks. Hence, we employed mechanochemical ball milling as a synthetic alternative to generate desired cyclodiphosph(III)azane compounds. On top of that, air- and moisture-stable cyclodiphosph(V)azanes are synthesized in orthogonal one-pot one-step manner (Chapter 3). In general, the nucleophilic substitutions of dichlorocyclodiphosph(III)azanes result in formation of new P-N, P-O, P-S or P-C bonds. In this thesis, a new class of P-O(carboxyl) bond is further investigated via oxidation reactions (Chapter 4). Despite the vast examples of cyclodiphosphazanes known, they typically lack functionality for further reactions. Therefore, it hinders the exploration and development of potential applicability of cyclodiphosphazanes. With these inadequacies identified, ester has been introduced into the targeted cyclodiphosphazane frameworks in view to increase the utility. The isolated compounds were fully characterized and described in Chapter 5. Lastly, the syntheses of tris(cyclodiphosphazane) compounds are described along with that of a novel extended P2N2-based macrocycle (Chapter 6).